An investigation of factors affecting the distribution and abundance of phycoperiphyton in navigation pool no. 5, Upper Mississippi River - Luttenton, Mark Russell (My University, 1982)
Periphytometers with glass slide substrates were used to develop years of baseline data on community structure, cell density, biomass, pigment concentrations, and community physiology of the pycoperiphyton in Navigation Pool no. 5 of the Upper Mississippi River.
Keywords: Freshwater algae, Mississippi River, Navigation Pool no. 5.